2022
DOI: 10.1007/s00431-022-04395-x
|View full text |Cite|
|
Sign up to set email alerts
|

What does the evidence tell us? Revisiting optimal cord management at the time of birth

Abstract: A newborn who receives a placental transfusion at birth from delayed cord clamping (DCC) obtains about 30% more blood volume than those with immediate cord clamping (ICC). Benefits for term neonates include higher hemoglobin levels, less iron deficiency in infancy, improved myelination out to 12 months, and better motor and social development at 4 years of age especially in boys. For preterm infants, benefits include less intraventricular hemorrhage, fewer gastrointestinal issues, lower transfusion requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Delayed cord clamping results in a baby receiving 30 % more blood than a baby whose cord is clamped at birth [33,34]. In this study, the majority of women reported that the umbilical cord was clamped and cut in line with the evidence base.…”
Section: Discussionmentioning
confidence: 72%
“…Delayed cord clamping results in a baby receiving 30 % more blood than a baby whose cord is clamped at birth [33,34]. In this study, the majority of women reported that the umbilical cord was clamped and cut in line with the evidence base.…”
Section: Discussionmentioning
confidence: 72%
“…To justify separation at birth by highlighting the need for resuscitation should no longer be accepted. A growing body of evidence reports that intact cord resuscitation supports the process of physiologic neonatal transition and is beneficial for non-vigorous newborn infants 22 , 23 . If motherside resuscitation cannot be practiced for maternal reasons, specially designed equipment or trolleys can facilitate resuscitation, in the same room, with the placental and cord circulation intact 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of blood loss at birth from ICC can be quite subtle or acute [53]. In a study examining the effects of a severe acute hemorrhage on late-term fetal sheep, Meyers and Rudolph (1991) found life-threatening effects following the removal of 40% of the fetal blood volume [54].…”
Section: Effect Of Blood Loss At Birth On the Fetus/newbornmentioning
confidence: 99%